Aerial photograph interpretation of the bourville landslide in South Wales, United Kingdom - Wan Zuhairi Wan Yaacob, (Universiti Kebangsaan Malaysia, 2003)
Aerial photograph interpretation was used to investigate the activity of the Bournville landslide in South Wales, United Kingdom. The information from the interpretation is useful for monitoring the movement and remediation of the landslide. The interpretation on several aerial photographs ranging from year 1946-1991 showed that the major movement had occurred mainly at the southern toe of the landslide. The southern toe of this landslide was regarded as the most critical and crucial part and need to be remediated before further failure could trigger the safety of the landslide.